Dissimilar microRNA-21 functions and targets in trophoblastic cell lines of different origin. (November 2015) - Chaiwangyen, Wittaya; Ospina-Prieto, Stephanie; Photini, Stella Mary; Schleussner, Ekkehard; Markert, Udo R.; Morales-Prieto, Diana M.
Graphical abstract: Highlights: Inhibition of miR-21 decreases cell proliferation, migration, and invasion in JEG-3 and HTR-8/SVneo cells and additionally, induces apoptosis in JEG-3 cells. Silencing of miR-21 enhances PDCD4 expression only in JEG-3 cells (not in HTR-8/SVneo cells). Silencing of miR-21 enhances PTEN expression only in HTR-8/SVneo cells (not in JEG-3 cells). Inhibition of miR-21 significantly increases phosphorylation of AKT in HTR-8/SVneo cells. Abstract: Trophoblast cells express a singular miRNA expression profile which varies during pregnancy and whose alteration may be associated with pregnancy complications. miR-21, a widely known oncomir, is highly expressed in human placenta but its role in regulating trophoblast cells remains unclear. The aim of this study was to investigate miR-21 functions and targets in HTR-8/SVneo immortalized trophoblast and JEG-3 choriocarcinoma cells, which are trophoblast cell models that differ in their cellular origin. Cells were transfected with miR-21-antagomir, -mimic or their respective controls. Following, cell proliferation (BrdU), migration (Transwell and scratch wound-healing assays), invasion (Matrigel assays) and apoptosis (flow cytometry, TUNEL assay and Western blotting) were assessed. Expression of the potential miR-21 targets phosphatase and tensin homolog (PTEN) and programmed cell death 4 (PDCD4) were analyzed by Western blotting. Inhibition of miR-21 decreased cell proliferation, migration, and invasion in JEG-3 and HTR-8/SVneo cells and additionally, induced apoptosis in JEG-3 cells. Silencing of miR-21 enhanced PDCD4 expression only in JEG-3 cells, and PTEN expression only in HTR-8/SVneo cells. Inhibition of miR-21 significantly increased phosphorylation of AKT in HTR-8/SVneo cells. In conclusion, miR-21 has cell-specific targets depending upon the origin of trophoblastic cells. Furthermore, miR-21 regulates major cellular processes including cell growth, migration, invasion and apoptosis suggesting that its impairment may lead to placental disorders.